2021
DOI: 10.3389/fphar.2021.708517
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent Time-Dependent Effects of Tetramethylpyrazine on Primary Neurological Disorders and Psychiatric Comorbidities

Abstract: The aim of this study was to investigate the time dependent effects of tetramethylpyrazine (TMP, main activity compound of Ligusticum chuanxiong Hort) on two neurological disorders and their neuropsychiatric comorbidities. 6 Hz corneal rapid kindling was used to induce epileptogenesis and the inflammatory pain was induced by intra-articular Complete Freund’s adjuvant (CFA) injection. The mechanical pain thresholds were measured using von Frey hair (D4, D11, D18, D25 after CFA first injection), and the vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…It also inhibits KA-induced epilepsy model in vivo and in vitro , and the underlying mechanisms involved neuroprotective effects, including the stabilization of the mitochondrial function, declining oxidative damage, and prevention of the loss of neurons in the hippocampal CA3 region ( 58 ). The enhanced hippocampal BDNF/ERK signaling alleviates the neuropsychiatric comorbidities in neurological diseases ( 59 ). In addition, TMP reduces pro-inflammatory factors, such as IL-2, IL-6, and tumor necrosis factor-α (TNF-α), which in turn decreases the PTZ-induced seizures in rat models ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits KA-induced epilepsy model in vivo and in vitro , and the underlying mechanisms involved neuroprotective effects, including the stabilization of the mitochondrial function, declining oxidative damage, and prevention of the loss of neurons in the hippocampal CA3 region ( 58 ). The enhanced hippocampal BDNF/ERK signaling alleviates the neuropsychiatric comorbidities in neurological diseases ( 59 ). In addition, TMP reduces pro-inflammatory factors, such as IL-2, IL-6, and tumor necrosis factor-α (TNF-α), which in turn decreases the PTZ-induced seizures in rat models ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, BDNF levels are decreased in the hippocampus of CSDS mice, and TMP treatment increased the BDNF levels and improves depressive symptoms in these mice; these findings shed light on the development of new antidepressants with higher efficacy and fewer side effects ( Jiang et al, 2015 ). This conclusion was further verified in a later study by Jiang et al (2015) , who suggested that TMP alleviated anxiety and depressive behaviors by increasing hippocampal BDNF/ERK expression ( Jiang et al, 2021 ).…”
Section: Molecular Mechanism Of Action Of Traditional Chinese Medicin...mentioning
confidence: 55%